Analisis Perkembangan Peserta Didik Dalam Meningkatkan Efektivitas Belajar Siswa Di SMP Plus Mambaus Sholihin Kradenan Grobogan - Mochamad Agus Cholil (https://journal.metanusantara.com/pedagogia, 2026)
Student development analysis is an important foundation in designing effective learning, but many schools still ignore the alignment between student development characteristics and applied learning strategies. This study aims to analyze the level of student development, measure the level of learning effectiveness, and test the relationship between the two variables at SMP Plus Mambaus Sholihin Kradenan Grobogan. The research uses a quantitative approach with a correlational type. The population was 240 students, with a sample of 150 students determined using the Slovin formula and taken through proportionate random sampling techniques. The research instrument is in the form of a Likert scale questionnaire that has been tested for validity and reliability. Data analysis using descriptive statistics and Pearson Product Moment correlation test with the help of SPSS 25. The results showed that student development was in the medium category (52%, mean=72.45), learning effectiveness was in the medium category (54.7%, mean=74.18), and there was a strong and significant relationship between student development and learning effectiveness (r=0.685, p=0.000, contribution 46.9%). These findings prove that the better the teacher's understanding of student development, the higher the learning effectiveness achieved. This study recommends the need to balance the development of students' cognitive, social-emotional, and moral aspects in daily learning practices